Decision Making Analysis of Plastic Bag Use Reduction Policy in Surabaya City - Nugroho, Devin Dwi (JPASDEV : Journal of Public Administration and Sociology of Development, 2024)
This journal article aims to investigate and analyse the policy decision-making related to reducing the use of plastic bags in Surabaya City. This analysis involves an in-depth understanding of the factors that influence policy decisions, the challenges faced, as well as the implications of the implemented policies. The method used in writing this article is a literature study. Literature research is a scientific activity carried out to explore research data or information. The results showed that the policy of reducing the use of plastic bags in Surabaya based on the view of the theory of policy implementation from George C. Edward III is that the communication aspect has not run properly. Edward III is that the communication aspect has not run optimally, the resource aspect is also still not carried out optimally, the disposition in the implementation of the use reduction policy is quite good in its cognition, and the bureaucratic structure aspect has run quite well.